Odpowiedzi

2010-03-02T15:19:11+01:00
H)
0,1x=-7
x=-70

zad. 2
a)
-3x=2x-10
-3x-2x=-10
-5x=-10
x=2

b)
2x-2=7-x
2x+x=7+2
3x=9
x=3

c)
10=4-2x
-2x=4-10
-2x=-6
x=3

d)
-(2x-1)=4
-2x+2=4
-2x=4-2
-2x=2
x=-1

e)
2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f)
2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7
t=-7

g)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
2010-03-02T15:20:23+01:00
H) 0,1x=-7
x=-70

a) -3x=2x-10
-3x-2x=-10
-5x=-10
x=2
b)2x-2=7-x
2x+x=7+2
3x=9
x=3
c) 10=4-2x
4-2x=10
-2x=10-4
-2x=6
x=-3
d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3
x=-2/3
e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7
t=-7
g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=18-18
0=0
2010-03-02T15:21:08+01:00
H]
0,1x=-7
x=-7:0,1
x=-70
zad.2]
a]-3x=2x-10
-3x-2x=-10
-5x=-10
x=-10:-5
x=2

b]2x-2=7-x
2x+x=7+2
3x=9
x=9:3
x=3
c]
10=4-2x
2x=4-10
2x=-6
x=6:2
x=-3
d]
-(2x-1)=4
-2x=4-1
-2x=3
x=3:-2
x=-1,5
e]
2(x+1)=x
2x-x=-2
x=-2
f]
2t-(3t+1)=6
2t-3t-1=6
-t=6+1
t=-7
g]
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h]
3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0